Impact of Ethanol Exposure on Survival and the Expression of Endogenous Antioxidants in Drosophila melanogaster - L.M Alif Fauzan Tamar; Nur Islamiah Syahrir; Khansa Khansa; Reski Amalia Rosa; Nadila Pratiwi Latada; Sri Wahyuni M; Nur Rahma Rumata; Risfah Yulianty; Mukarram Mudjahid; Firzan Nainu (International Journal of Biomedical Science and Travel Medicine, 2024)
Background Ethanol, a widely consumed psychoactive substance, disrupts cellular and molecular processes, leading to a range of adverse physiological effects. Prolonged exposure to ethanol has been associated with severe neurological disorders, underscoring the importance of investigating its toxicological impact. This study aims to evaluate the effects of ethanol exposure on the phenotypical characteristics of Drosophila melanogaster, with a particular focus on survival and the expression of endogenous antioxidant-related genes. Methods The study utilized an ethanol exposure assay on male w1118 flies, assessing survival and the expression of the sod1, sod2, and cat genes through reverse transcriptase quantitative PCR (RT-qPCR). Results Ethanol exposure negatively affected survival in a concentration-dependent manner, with lower survival rates observed in Drosophila groups exposed to higher ethanol concentrations. Additionally, molecular analysis highlighted the significant role of the endogenous antioxidant gene cat in promoting survival in Drosophila under ethanol exposure. Conclusion The findings of this study indicate that ethanol exposure is lethal to D. melanogaster in a concentration-dependent manner, with catalase playing a key role in mitigating its toxic effects and enhancing fly survival.